Distribution patterns, conservation status and suitable habitat areas of highly valuable medicinal plants in China - Gao, Xiuli; Gao, Jiejing; Gadagkar, Sudhindra R.; Yao, Ruyu; Li, Yiheng; Jin, Sanling; Buhe,; Wei, Jianhe; Zhang, Bengang; Yu, Shengxiang; Zheng, Zhirong; Qi, Yaodong (Frontiers in Plant Science, 2025)
Medicinal plants represent a critical component of biodiversity. This study focuses on the most valuable species listed in the Red Data Book of Chinese Medicinal Plants (RCMPs) to analyze their distribution patterns, identify diversity hotspots, assess conservation status, and predict suitable habitats across China. Results reveal that RCMPs are primarily concentrated in southwestern China, particularly the Qilian Mountains, Qinling-Bashan Mountains, and southeastern Xizang. As the hotspot threshold increases, the conservation effectiveness of provincial nature reserves is surpassed by that of national reserves. Concurrently, overall effectiveness declines, with over 16.43% of hotspot grids (containing >91.48% of species) remaining unprotected, indicating persistent conservation gaps in southwestern China and Xinjiang. Predictive modeling suggests a potential decrease in RCMPs richness in southeastern and central China. Under the RCP 2.6 and 8.5 scenarios for 2070, approximately 42.99% and 57.01% of RCMPs are projected to experience habitat contraction and expansion, respectively. Based on these findings, we propose a comprehensive priority conservation framework to inform future protection planning and promote the long-term conservation and sustainable use of China’s medicinal plants.